NONOSHIRI NO KOTOBA PADA ANIME TONARI NO KAIBUTSU-KUN KARYA ROBICO - Jeline Sabetti Br Sitepu; Arza Aibonotika; Intan Suri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The purpose of this research is to explain what are the classification from various forms of swear words in the anime “Tonari No Kaibutsu-Kun”. This research was conducted using a qualitative approach and the type of the research is a descriptive research. The method that was used by the researcher in collecting the data in this research is the note-taking method. First, the researcher downloaded 13 episodes of the anime “Tonari No Kaibutsu-Kun” that was made by Robico in Netflix and then searched, listened and recorded the data found. The results that were obtained from the 13 episodes of the anime “Tonari No Kaibutsu-Kun” that was made by Robico, 17 swear words were found which resulted with 5 classifications.Key Words: Swearing, Classification, Anime Tonari No Kaibutsu-Kun